2017
DOI: 10.1155/2017/4931749
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Analysis of Reinforced Concrete Simply Supported Beam versus Variation Temperature

Abstract: It is well known that temperature has great influence on modal characteristics of bridges. The relationship between them has been studied by using statistical mathematics, numerical analysis, and field's monitoring methods, which have relatively narrow applicability. Therefore, it is necessary to analyze their relationship theoretically. In this paper, the relationship between temperature and modal characteristics of the simply supported beam is investigated based on theoretical calculation method. Firstly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The experimental and the calculated results are both listed in Table 1, in which the results in bold are the change rates of the morning and noon frequencies relative to the night frequencies. The air temperature both under the bridge (Tu) and over the bridge (To) during the test were also recorded and listed in Table 1, and the temperature distribution of the whole structure can be calculated by the widely used thermal analysis model (Liu et al, 2017; Zhang et al, 2021).
Figure 7.Amplitude spectrums of 1# accelerometer at different times of day: (a) Spectrums graph, (b) Local enlarging graph, (c) Local enlarging graph.
…”
Section: Engineering Verification and Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental and the calculated results are both listed in Table 1, in which the results in bold are the change rates of the morning and noon frequencies relative to the night frequencies. The air temperature both under the bridge (Tu) and over the bridge (To) during the test were also recorded and listed in Table 1, and the temperature distribution of the whole structure can be calculated by the widely used thermal analysis model (Liu et al, 2017; Zhang et al, 2021).
Figure 7.Amplitude spectrums of 1# accelerometer at different times of day: (a) Spectrums graph, (b) Local enlarging graph, (c) Local enlarging graph.
…”
Section: Engineering Verification and Numerical Examplesmentioning
confidence: 99%
“…However, it is very difficult to describe the modal characteristics of bridges in theory at different temperatures, and there is little research paying attention to this. Herein, a theoretical method of the simply supported beam under the effect of temperature is proposed by our research group, which considers the temperature-induced change in elastic modulus, deflection and shear stiffness of bearings (Liu et al, 2017). In addition, a discussion is conducted around the effects of different temperature modes on the modal characteristics of Timoshenko beam, which leads to exact solution in closed form (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several bridges were studied for vibration analysis. A detailed report (Gaunt and Sutton, 1981) about bridges in the USA presented frequency and acceleration for 62 bridges that were spanning less than 30 m. A problem with the change of frequency during the day was identified (Liu et al, 2017) because of several factors, one of which was the temperature change during the day or the season. Another study identified the temperature variation in seasonal change (Magalha˜es et al, 2012).…”
Section: Energy Harvesting For Bhm Systemsmentioning
confidence: 99%
“…The bridges were of span less than 30 meters. The conducted study of bridges identified another problem, that was the frequency change with different factors one of which is change with temperature (Liu et al, 2017) during day time as well as with season (Magalhães et al, 2012). This necessitated a broad band device for energy harvesting.…”
Section: Low Frequency and Low Acceleration Vibration Energy Harvementioning
confidence: 99%